2015
DOI: 10.1259/bjr.20140865
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score in healthy ageing

Abstract: The study reports TBS values of a selectively enrolled Italian healthy population, ranging from younger to older ages and including males as a reference standard. Moreover, links between body composition and TBS are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 38 publications
5
26
2
Order By: Relevance
“…Our data are consistent with a recent study in a healthy Italian population across a wide age-spectrum that found no association between TBS and lean mass [40]. …”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with a recent study in a healthy Italian population across a wide age-spectrum that found no association between TBS and lean mass [40]. …”
Section: Discussionsupporting
confidence: 93%
“…The correlation between TBS and BMI does vary significantly by study. Kim and colleagues (18) reported a positive correlation 44( r =0.10) between TBS and BMI in a study of 1474 postmenopausal Korean women (Lunar DXA); Bazzocchi and colleagues (19) reported no correlation in a study of 250 Italian men and women (Lunar DXA); Sritara and colleagues (9) reported a weak negative correlation in a study of 848 Thai men and women (Hologic DXA); and Romagnoli and colleagues (20) reported a negative correlation in a study of 87 Italian men (Hologic DXA). Finally, McCloskey and colleagues (21) performed a large meta-analysis of studies of men and women of different ethnic origins (both Hologic and Lunar DXA), and reported an overall weaker negative correlation between TBS and BMI ( r =−0.16) than what we have found in the MrOS study population.…”
Section: Discussionmentioning
confidence: 98%
“…These deviations should be quantified, for example, in the form of (parametric or non-parametric) percentiles, similar to the Z-score or T-score of bone density. 26 However, no standard or reference values for body posture currently are published for healthy female subjects; reference values of the upper body posture for healthy men have been published only recently. 27 Also, classifications of the severity of posture deviations are only possible when deviations from standard or reference values are quantified.…”
Section: Introductionmentioning
confidence: 99%